Meta-Analysis on Zakat Index - Irma Durrotun Niswah (Tamkin Journal, 2022)
This study tries to review the research around zakat index on reputable journal. It uses descriptive statistical analysis based on selected 35 article publications or paper related to zakat index, with national and international journal. The entire sample journal publications have published for nine years from 2012 to 2020. The Results show that zakat index research study case is still dominated by Indonesia (25 study), following by Malaysia (8 study) and others. In addition, the Had Kifayah, CIBEST Index, and Zakat Village Index are the examples of zakat index implementation. Meanwhile, Puskas Baznas is the most active institution in developing zakat indexes in the world based on literatures.